(untitled) (Journal of the College of Basic Education, 2022)
LiDAR technology is one of the modern technologies that can be obtained through remote or proximity sensors in geographical studies and represented a quantum leap in those studies in terms of the value of the results that can help obtain them through analysis, interpretation and high flexibility in the diversity of applications. With its different dimensions, which are related to the geographical disciplines in general and the natural geography in particular, this study came to shed light on this technique and its applications in support of natural geographic studies and to reinforce what can be reached in terms of results or wills to make decisions about the various problems facing societies, the environment and spatial planning, and the study aims to Explanation of this technology and its most prominent applications used in natural geographic studies and the means to achieve this. The study dealt with clarifying this technology, how to obtain it and its technical uses, as well as technical applications and data processing using appropriate programs, most notably the ArcGIS program to be a clear action plan for researchers to invest this technology and its applications to harness Natural geographical studies of community service.